IL‐33 polymorphisms are associated with increased risk of hay fever and reduced regulatory T cells in a birth cohort. Issue 7 (12th July 2016) - Schröder, Paul C.; Casaca, Vera I.; Illi, Sabina; Schieck, Maximilian; Michel, Sven; Böck, Andreas; Roduit, Caroline; Frei, Remo; Lluis, Anna; Genuneit, Jon; Pfefferle, Petra; Roponen, Marjut; et al.
Abstract: Background: IL‐33 polymorphisms influence the susceptibility to asthma. IL‐33 indirectly induces Th2‐immune responses via dendritic cell activation, being important for development of atopic diseases. Furthermore, IL‐33 upregulates regulatory T cells (Tregs), which are critical for healthy immune homeostasis. This study investigates associations between IL‐33 polymorphisms during the development of childhood atopic diseases and underlying mechanisms including immune regulation of Tregs. Methods: Genotyping of IL‐33 ‐polymorphisms (rs928413, rs1342326 ) was performed by MALDI‐TOF‐MS in 880 of 1133 PASTURE/EFRAIM children. In 4.5‐year‐old German PASTURE/EFRAIM children (n = 99), CD4 + CD25 high FOXP3 + Tregs were assessed by flow cytometry following 24‐h incubation of PBMCs with PMA/ionomycin, LPS or without stimuli (U). SOCS3, IL1RL1, TLR4 mRNA expression and sST2 protein levels ex vivo were measured in PASTURE/EFRAIM children by real‐time PCR or ELISA, respectively. Health outcomes (hay fever, asthma) were assessed by questionnaires at the age of 6 years. Results: rs928413 andrs1342326 were positively associated with hay fever (OR = 1.77, 95%CI = 1.02–3.08; OR = 1.79, 95%CI = 1.04–3.11) and CD4 + CD25 high FOXP3 + Tregs (%) decreased in minor allele homozygotes/heterozygotes compared to major allele homozygotes (p(U) = 0.004; p(LPS) = 0.005; p(U) = 0.001; p(LPS) = 0.012). SOCS3 mRNA expression increased in minor allele homozygotes and heterozygotes compared with major allele homozygotes for both IL‐33 ‐polymorphisms (p(rs928413 ) = 0.032, p(rs1342326 ) = 0.019) and negatively correlated to Tregs. Conclusions: IL‐33 ‐polymorphismsrs928413 andrs1342326 may account for an increased risk of hay fever with the age of 6 years. Lower Tregs and increased SOCS3 in combined heterozygotes and minor allele homozygotes may be relevant for hay fever development, pointing towards dysbalanced immune regulation and insufficient control of allergic inflammation. Abstract :